Karakteristik Individu, Karakteristik Pekerjaan, Karakteristik Organisasi dan Kepuasan Kerja Pengurus yang Dimediasi oleh Motivasi Kerja (Studi pada Pengurus KUD di Kabupaten Sleman) (Jurnal Manajemen dan Kewirausahaan, 2009)
KUD’s success in making the members prosperous depends very much on the management satisfaction. The management work satisfaction are influenced by the management job characteristic. Sample are taken by cluster sampling with 137 samples, covering management of some KUD in Sleman district consisting of supervisors, chairmen, treasurers, secretaries, managers. Individual caracteristic, job characteristic and organizational characteristic are directly influential to the management satisfaction, with management motivation as mediator.